PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS II SDN WONOSARI - Astuti, Susi Widia; Susanto, Bahtiyar Heru (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to determine (1) the validity of the teaching materials, (2) the teacher's response, and (3) the effectiveness of the teaching materials on increasing the learning interest of second-grade students at SDN Wonosari. This study applied the Research and Development method, referring to the Borg and Gall model. It follows nine stages: (1) identifying potential and problems, (2) information gathering, (3) product design, (4) design validation, (5) product revision, (6) small-scale trials, (7) product revision, (8) large-scale trials, and (9) final product. Data collection techniques used interviews, documentation, and questionnaires. The development results show that (1) the teaching materials were categorized as very valid, with a final score of 100 from media experts and 93.75 from subject matter experts; (2) teacher responses were categorized as very practical, with a final score of 93.75; and (3) the developed product was effective in increasing the learning interest of second-grade students at SDN Wonosari, as evidenced by the students' average questionnaire score increasing from 41.50 before using the materials to 47.05 after using the materials, reflecting a 13.37% improvement in learning interest.